Influence of an Approach to External Business Environment in Delhi: The Role of Environmental Analysis in Strategic Management: A Case Study of Delhi (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Environmental management, a term encompassing environmental planning, protection, monitoring, assessment, research, education, conservation and sustainable use of resources, is now accepted as a major guiding factor for sustainable development at the regional and national level. It is now being increasingly recognized that environmental factors and ecological imperatives must be in built to the total planning process if the long-term goal of making industrial development sustainable is to be achieved. Here we will try to define and discuss the role of Environmental Analysis in the strategic management process of organization in Delhi. The present complex world require as far as is feasible, it consider impact of important factors related to organizations in strategic planning. The strategic planning of business includes all functional subdivisions and forwards them in a united direction. One of these subsystems is human resource management. Strategic human resource management comes after the strategic planning, and followed by strategic human resource planning as a major activity in all the industries in Delhi. In strategic planning, it can use different analytical methods and techniques in Delhi.